Training And Mentoring Of The Creative Women’s Group Tanginas To Develop Innovative Bamboo Shoot-Based Products In Cimareme Village, West Bandung Regency - Dewi Fitriani Nurillah; Syalwa Nazhifah Aulya Wanda; Nisa Auliya; Ridwan Ridwan; Erna Herlinawati; Devyanthi Syarif; Tjipto Sajekti (Universitas INABA, 2024)
Community empowerment through the utilization of local potential is the focus of the community service program. This program aims to empower the Creative Women's Group Tanginas in Cimareme Village, West Bandung Regency, by optimizing bamboo shoots as raw materials for innovative products. Various training and mentoring are carried out to improve digital marketing skills, standard operating procedures, and financial reporting. Evaluation using pre-tests and post-tests showed a significant increase in participants' knowledge and skills, especially in utilizing digital platforms such as websites for branding and sales. This program has succeeded in increasing production capacity, standardizing product quality, and expanding market reach, thus contributing to the sustainability of the local economy